A Guide to the Tadpoles of Borneo - Indraneil, Das; Alexander, Haas; Stefan T., Hertwig; Pia, Bublies; Reinhard, Schulz-Schaeffer (Tredition GmbH, 2022)
The monograph describes 99 species of amphibian larvae from the island of Borneo.